Nitric oxide(II) releasing polymers - Parzuchowska, B.; Parzuchowski, P. (Polimery, 2014)
The paper is a literature review concerning the polymeric materials capable of generating nitric oxide(II). The role of nitric oxide (NO) in an organism comprise the protective, regulatory, and signaling functions. NO molecule is involved in the regulation of blood pressure, clotting, neurotransmission and the immune response. The problems associated with chemical bonding of NO donor molecules — diazeniumdiolates — to the polymeric chains or filler particles have been discussed. The basic information on the synthesis, properties and methods of the investigation of diazeniumdiolates was given. The modifications of polymeric materials by introducing of nitric oxide donors to the polymers commonly regarded as biocompatible such as: polysiloxanes, polyurethanes, polyacrylates or PVC have been presented. The best results were obtained for the polymers of low polarity such as polysiloxanes, modified silica or acrylic polymers, which are able to generate several µmol of NO per mg of the material. The largest amounts of nitric oxide were released from low-polarity polymers modified with diazeniumdiolates of the anionic type, whereas the generation of zwitterionic diazeniumdiolates have not produced satisfactory results. Some of the described polymeric systems were capable of delivering nitric oxide at an almost negligible nmol per mg level. Efficient NO flux generated by biological systems, however, is so small that even such a weak nitric oxide donors may find further applications.